PENGARUH KARAKTERISTIK DEWAN KOMISARIS SEBAGAI MEKANISME GOOD CORPORATE GOVENANCE TERHADAP TINGKAT KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - LIMANTAUW, SHIRLY (Universitas Katolik Widya Mandala Surabaya, 2012)
Accounting conservatism in corporate applied in varying degrees. One of the factors that determine the level of conservatism is the commitment of management and internal party companies to provide transparent information, accurate and not misleading to investors, which is the implementation of good corporate governance. In carrying out its oversight duties, the board requires quality information, so that conservatism can help the board of directors in improving the quality of corporate financial statement information and reducing agency costs. This study aims to analyze the influence of the characteristics of the board of commissioners as corporate governance mechanisms on the level of accounting conservatism. Characteristics of the board used is the proportion of independent commissioner and the commissioner of stock ownership by affiliated. This study uses a measure of accruals to measure the level of conservatism, as well as profitability and leverage as control variables. This study used a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) of 2008 to 2010. Samples were selected using purposive sampling method, and obtained a sample of 56 companies. Hypothesis testing is done by regression methods that meet the assumptions BLUE (Best Linear Unbiased Estimate). The results of this study indicate that the proportion of independent commissioners have no influence to the level of accounting conservatism, while the ownership of shares by the commissioner affiliated significantly negative effect on the level of accounting conservatism.